ASSESSING THE QUALITY OF MICROSERVICE AND MONOLITHIC-BASED ARCHITECTURES: A SYSTEMATIC LITERATURE REVIEW - Saad Hussein; Mariam Lahami; Mouna Torjmen (Operational Research in Engineering Sciences: Theory and Applications)
Building a scalable system has been found to be an even greater challenge than developing software in general, due to the complexity and otherwise involved in its development. Whereas monolithic applications are made of big entities that are developed together, independent services sum up the arrays of a micro services-based architecture. This research work will therefore come up with the framework that would be used in supporting the migration of organizations and industries into micro services. This approach gives companies the evaluative methodology for assessing their adoption of micro services. This approach enables an enterprise to measure its capacity for the effective implementation of micro services using quality criteria. An SLR was conducted, as we selected 48 relevant research papers published during the last four years, 2020–2023. Findings on the quality characteristics of monolithic versus micro services-based systems were collated to demonstrate how suitable quality attribute metrics help evaluate these architectural approaches more effectively. Key indicators can thus help transition from monolithic architectures to a micro services architecture. The outcome of the literature review brings forth the key quality attributes in addition to their sub-characteristics as follows: performance, scalability, coupling, cohesion, deployment, security, development, complexity, maintainability, and availability. The results display that interest among researchers in quality-driven micro services migration is growing while an appreciable number of studies are centered on quality enhancement as the main objective of strategies of migration.